2018
DOI: 10.5539/enrr.v8n3p69
|View full text |Cite
|
Sign up to set email alerts
|

Butterfly Diversity: An Indicator for Environmental Health within Tarkwa Gold Mine, Ghana

Abstract: Many human societies, rely on proceeds from mining of metals and fossil fuels for income generation as well as resource supplies from biodiversity. However, these mining activities are in conflict with and threaten the sustainable utilisation and conservation of biodiversity. We used butterflies, a known bioindicator species as surrogates to measure the level of change in vegetation within Tarkwa Gold Mines (TGM) in Ghana. Butterfly assemblages were sampled within the concession and characterised in terms of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 43 publications
1
8
0
1
Order By: Relevance
“…The present investigations recorded diversity indices of seventeen insect’s families with in six orders collected in treated traps suggested significant (P < 0.05) abundance ranged 24.70–77.78%. These results are in agreement with the scientists who reported that the insect populations of Noctuidae, Pieridae, Lycaenidae, Nymphalidae, Hesperiidae families increased by sugar fermented traps [ 30 , 67 , 68 ]. Our results suggested that the height of webs (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…The present investigations recorded diversity indices of seventeen insect’s families with in six orders collected in treated traps suggested significant (P < 0.05) abundance ranged 24.70–77.78%. These results are in agreement with the scientists who reported that the insect populations of Noctuidae, Pieridae, Lycaenidae, Nymphalidae, Hesperiidae families increased by sugar fermented traps [ 30 , 67 , 68 ]. Our results suggested that the height of webs (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…As a result, biomonitoring approaches have become more attractive for assessing the health of aquatic ecosystems because they are relatively cheaper. Biomonitoring is using sensitive species often referred to as indicator species for quantitative and or qualitative assessment of the performances of physical or biological systems (Wu et al, 2017;Zhou, Zhang, Fu, Shi, & Jiang, 2008) especially when they are affected by anthropogenic activities such as farming and mining (Adu-Acheampong, Bazelet, & Samways, 2016;Kyerematen et al, 2018a;Kyerematen, Kaiwa, Acquah-Lamptey, Adu-Acheampong, & Andersen, 2018b). Simple indices such as the presence or absence of a species, richness of a group or abundance of a species can be used as surrogates to measure pollution or change in conditions within riverine communities (D'costa, Shyama, Praveen Kumar, & Furtado, 2018;Łuczyńska, Paszczyk, & Łuczyński, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The second site at Yawmatwa CREMA (YS2) was the most even (J' = 0.936) in terms of species distribution. (Larsen 1994(Larsen , 2006 Butterfly assemblage in an area is determined by vegetation cover and diversity of the vegetation present (Addo-Fordjour et al 2015;Kyerematen et al 2018;Serrat et al 2015;Ubach et al 2020). The ongoing initiative by the Netherlands Development Organization (SNV), to practice the Shaded Cocoa Agroforestry (SCAF), has provided vegetation cover and protected the habitats of species in these areas which probably has accounted for the high diversity of butterfly species here.…”
Section: Resultsmentioning
confidence: 99%
“…Diversity indices were compared as a form of quantitative assessment of sites (Kyerematen et al 2018). The diversity of butterfly species was measured using the Shannon-Weiner Diversity Index.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation